Uncommon sites of cervical cancer metastases - Moszyńska-Zielińska, Małgorzata; Hejwowska, Jolanta; Sobotkowski, Janusz (Menopause Review/Przegląd Menopauzalny, 2006)
Cervical cancers spreads usually by local infiltration and by lymphatic and blood vessels. Metastases occurence mostly depends on tumour size and clinical stage. Hematogenous metastases arise in the very captious manner. They could manifest themselves even more than 5 years after completion of therapy. Three cases of rare sites metastases of cervical cancer were showed. Described method of treatment and survival time of patients with subcutaneuos arm tissue, cerebellum, bones and liver metastases. These observations remind us to be watchful during longtime clnical observation in cured patients and be aware of possibility of uncommon distant metastases even many years after oncologcal treatment.